2016
DOI: 10.5194/amt-9-1871-2016
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of aerosol optical depth in the visible range with a Brewer spectrophotometer in Athens

Abstract: Abstract.A MkIV Brewer spectrophotometer has been operating in Athens since 2004. Direct-sun measurements originally scheduled for nitrogen dioxide retrievals were reprocessed to provide aerosol optical depths (AODs) at a wavelength of about 440 nm. A novel retrieval algorithm was specifically developed and the resulting AODs were compared to those obtained from a collocated Cimel filter radiometer belonging to the Aerosol Robotic Network (AERONET). The series are perfectly correlated, with Pearson's correlati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 63 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…Brewer ozone data for Athens have been analyzed in recent studies [51,52]. In addition, the instrument was used to derive AOD in the visible part of the solar spectrum [53]. For the first time in this study, we analyzed spectral UV irradiance measurements at 324 nm from the Athens Brewer instrument, for the period January 2009 to December 2014.…”
Section: Brewer Spectrophotometermentioning
confidence: 99%
“…Brewer ozone data for Athens have been analyzed in recent studies [51,52]. In addition, the instrument was used to derive AOD in the visible part of the solar spectrum [53]. For the first time in this study, we analyzed spectral UV irradiance measurements at 324 nm from the Athens Brewer instrument, for the period January 2009 to December 2014.…”
Section: Brewer Spectrophotometermentioning
confidence: 99%
“…In the comparison between Brewer and OMI data the scaled correlation (RHOs) was calculated (Diémoz et al, 2016) to exclude the possibility that the source of the correlation is a common cycle (e.g. the annual cycle).…”
Section: Statistical Parametersmentioning
confidence: 99%
“…Kouremeti et al (2014) found percentages between 46 and 88 % when comparing independently calibrated Brewer and Cimel instruments at wavelengths between 306 and 320 nm (extrapolated from 340 nm in the case of the Cimel). Diémoz et al (2016) calibrated a Mk IV Brewer with respect to a Cimel instrument at 437 nm, finding that 90 % of the observations were within the WMO traceability limit once a temperature correction for the Brewer was included. Carlund et al (2017) reported percentages between 85.6 and 97 % between UVPFR and Brewer photometers operating in the 306-320 nm range, the Brewer being calibrated using the UVPFR's AOD as reference.…”
Section: Brewermentioning
confidence: 99%
“…Previous works have already demonstrated the feasibility of using Brewer spectrophotometers, usually devoted to the measurement of the total ozone column (TOC) and UV irradiance, to determine the aerosol optical depth (AOD); see, e.g., Harrison and Michalsky (1994), , Marenco et al (1997), Carvalho and Henriques (2000), , Marenco et al (2002), Cheymol and De Backer (2003), Arola and Tapani (2004), Gröbner and Meleti (2004), Savastiouk and McElroy (2004a), Savastiouk and McElroy (2004b), Silva and Kirchhoff (2004), Kazadzis et al (2005), Savastiouk (2006), Sellitto et al (2006), Kazadzis et al (2007), De Bock et al (2010), Kumharn (2010), Kumharn et al (2012), De Bock et al (2014), Kumharn et al (2015), Rodriguez-Franco (2015), Diémoz et al (2016), and Kumharn and Hanprasert (2016). Although Brewer spectrophotometers can be used to retrieve AOD at longer wavelengths, in their standard operational mode most instruments can only produce data in the 300-320 nm range.…”
Section: Introductionmentioning
confidence: 99%